Flexible blue-light fiber amplifiers to improve signal coverage in advanced lighting communication systems - Bastos, Ana R. (2021)
Visible-light communication (VLC) based on white light-emitting diodes has recently attracted much attention to provide high-bitrate data communication in indoor environments. One of the remaining challenges to be resolved to enable the proliferation of VLC systems is related to channel attenuation and multiple path fading. Here, we introduce an advanced VLC system integrating an optical amplifier as a promising solution to overcome channel impairments, providing high bitrate coverage. The optical amplifier is a flexible fiber based on a poly(fluorene)-based lumophore doped within a di-ureasil organic-inorganic hybrid. Optical amplification is demonstrated for pre-amplifier and relay node scenarios, yielding a maximum gain of 5.9 ± 0.2 dB and 3.7 ± 0.2 dB, respectively, establishing the proposed approach as a promising cost-effective solution for VLCs. Additionally, numerical simulations show, for a realistic environment, a 207% improvement in the coverage area, using existing lighting infrastructure without extra cost.